Effect of niacin supplementation on milk production and ketosis of dairy cattle - G. Dufva; E. Bartley; A. Dayton; D. Riddell (Kansas Agricultural Experiment Station Research Reports, 1984)
Two lactation trials were undertaken to evaluate the effect of a niacin supplement on milk production and 'the physiological symptoms of ketosis. Blood ketone and non-esterified fatty acid levels were lower and blood glucose concentrations higher in niacin-supplemented cows. These trends were exhibited regardless of whether supplementation began 2 wk prepartum or immediately after calving. A 6 g daily dose was found to be of equal or higher benefit than a 12 g supplement. Cows gi ven niacin consistently produced more milk than controls, though the difference was small.; Dairy Day, 1984, Kansas State University, Manhattan, KS, 1984;
Keywords: Kansas Agricultural Experiment Station contribution; no. 85-116-S; Report of progress (Kansas Agricultural Experiment Station); 460; Dairy; Niacin; Milk production; Ketosis